Mental Well-Being Training for Mathematics Teachers to Deal with Online Learning Period - Alfiandy Warih Handoyo; Evi Afiati; Rochani Rochani; Indah Juwita Sari (Jurnal Pendidikan Indonesia Gemilang, 2023)
The online learning process leaves many problems in its implementation. One problem is the teacher's unpreparedness to manage stress due to implementing online learning activities. This study aimed to improve mathematics teachers' readiness to deal with pressure during online learning activities. The method used is action research which refers to 5 aspects of stress. The subjects in this study were 30 mathematics teachers who were members of the Serang Regency Subject Matter Teacher Forum. Indicators of success are participants who experience each aspect under eight people. Activities carried out in 2 cycles. The test results showed that the average score on the physical aspect changed from 15 people at the beginning of the assessment to 9 people in the first posttest and seven people in the second posttest. Furthermore, the emotional aspects of 14 people became nine people in the first posttest and six people in posttest 2. The mental aspect changed from 10 people in the pretest to 8 people in posttest 1 and five people in posttest 2. Behavioral aspects from 17 people to 10 people in the first posttest and seven people in the second posttest. The last aspect, spiritual, from 8 people, turned into four people in the first post-set and three people in the second post-set. Based on the data, training activities can reduce teacher stress levels during the online learning period.